Impact of the abolition of copayments on the GP-centred coordination of care in Bavaria, Germany: analysis of routinely collected claims data - Werner Maier; Antonius Schneider; Lars Schwettmann; Ewan Donnachie; Martin Tauscher; Roman Gerlach; Klaus Linde; Michaela Olm (BMJ Open)
Objectives In 2012, Germany abolished copayment for consultations in ambulatory care. This study investigated the effect of the abolition on general practitioner (GP)-centred coordination of care. We assessed how the proportion of patients with coordinated specialist care changed over time when copayment to all specialist services were removed. Furthermore, we studied how the number of ambulatory emergency cases and apparent ‘doctor shopping’ changed after the abolition.Design A retrospective routine data analysis of the Bavarian Association of Statutory Health Insurance Physicians, comparing the years 2011 and 2012 (with copayment), with the period from 2013 to 2016 (without copayment). Therefore, time series analyses covering 24 quarters were performed.Setting Primary care in Bavaria, Germany.Participants All statutorily insured patients in Bavaria, aged ≥18 years, with at least one ambulatory specialist contact between 2011 and 2016.Primary and secondary outcome measures Primary outcome was the percentage of patients with GP-coordinated care (every regular specialist consultation within a quarter was preceded by a GP referral). Secondary outcomes were the number of ambulatory emergency cases and apparent ‘doctor shopping’.Results After the abolition, the proportion of coordinated patients decreased from 49.6% (2011) to 15.5% (2016). Overall, younger patients and those living in areas with lower levels of deprivation showed the lowest proportions of coordination, which further decreased after abolition. Additionally, there were concomitant increases in the number of ambulatory emergency contacts and to a lesser extent in the number of patients with apparent ‘doctor shopping’.Conclusions The abolition of copayment in Germany was associated with a substantial decrease in GP coordination of specialist care. This suggests that the copayment was a partly effective tool to support coordinated care. Future studies are required to investigate how the gatekeeping function of GPs in Germany can best be strengthened while minimising the associated administrative overhead.